2019
DOI: 10.1108/ijbm-03-2019-0096
|View full text |Cite
|
Sign up to set email alerts
|

The effect of service quality and customer satisfaction on customer loyalty

Abstract: Purpose The purpose of this paper is to investigate the impact of customer satisfaction, service quality, the perceived value of services, corporate image and corporate reputation on customer loyalty and their relationship in the Turkish banking industry. Mediation effects of the perceived value and corporate image and reputation are also studied. Understanding the relationships between the determinants of customer loyalty toward the bank helps management to use corporate image and reputation more effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(105 citation statements)
references
References 96 publications
9
91
0
5
Order By: Relevance
“…This might occur when customers perceive they are receiving the consistent and quality service they expect; thus, the bank's image became less important. Concerning mediating or indirect effects, perceived value is a strong mediator between service quality and customer loyalty, supporting the findings of Ozkan et al (2019). It can be inferred from this that once a bank customers believe they are receiving reasonable value for money in comparison with other banks, they become attached to and will remain with their service provider.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This might occur when customers perceive they are receiving the consistent and quality service they expect; thus, the bank's image became less important. Concerning mediating or indirect effects, perceived value is a strong mediator between service quality and customer loyalty, supporting the findings of Ozkan et al (2019). It can be inferred from this that once a bank customers believe they are receiving reasonable value for money in comparison with other banks, they become attached to and will remain with their service provider.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, several studies have shown that service quality exerts a significant positive impact on both corporate image and perceived value (Bakar et al, 2017;Zameer, Tara, Kausar, & Mohsin, 2015), which in turn notably affect behavioral intentions, such as long-term relationships, word-of-mouth marketing, and re-patronization (Bakar et al, 2017;Lewis & Soureli, 2006;Nguyen & Leblanc, 1998). As a result, service quality indirectly affects behavioral intentions via customer satisfaction (Cronin, Brady, and Hult, 2000;Lewis & Soureli, 2006;Nguyen & Leblanc, 1998) as well as on customer satisfaction and loyalty through corporate image and perceived value (Cronin, Brady, and Hult, 2000;Lewis & Soureli, 2006;Ozkan, Süer, Keser, & Kocakoç, 2019). In addition, perceived value exerts a two-way mediating effect: between customer satisfaction to corporate image, and perceived quality to corporate image (Nguyen & Leblanc, 1998).…”
mentioning
confidence: 99%
“…Then, H2 is accepted. This finding is consistent with the prior studies (Amin and Zahora Nasharuddin, 2013;Demirci Orel and Kara, 2014;Mohamed and Azizan, 2015;Özkan et al, 2019;Su et al, 2016) that there is a relationship between health care service quality and patient satisfaction. When health care service is delivered and perceived as high-quality service, patients' expectations will be more fulfilled, patients will give positive emotional evaluation concerning the service, and patients satisfaction will come as a result.…”
Section: Discussionsupporting
confidence: 93%
“…There are sample studies on customer satisfaction with its relationship with the service quality as a major construct (Özkan et al, 2019;Huang et al, 2019). Raza et al (2020) and Joudeh (2017) found that all the dimensions had a significant and positive influence on the satisfaction of the customer.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%